Kinetics of the Human Papillomavirus Type 16 E6 Antibody Response Prior to Oropharyngeal Cancer. (22nd March 2017) - Kreimer, Aimée R.; Johansson, Mattias; Yanik, Elizabeth L.; Katki, Hormuzd A.; Check, David P.; Lang Kuhs, Krystle A.; Willhauck-Fleckenstein, Martina; Holzinger, Dana; Hildesheim, Allan; Pfeiffer, Ruth; Williams, Craig; Freedman, Neal D.; et al.
Abstract: Background: In a European cohort, it was previously reported that 35% of oropharyngeal cancer (OPC) patients were human papillomavirus type-16 (HPV16) seropositive up to 10 years before diagnosis vs 0.6% of cancer-free controls. Here, we describe the kinetics of HPV16-E6 antibodies prior to OPC diagnosis. Methods: We used annual serial prediagnostic blood samples from the PLCO Cancer Screening Trial. Antibodies to HPV were initially assessed in prediagnostic blood drawn at study enrollment from 198 incident head and neck cancer patients (median years to cancer diagnosis = 6.6) and 924 matched control subjects using multiplex serology, and subsequently in serial samples (median = 5/individual). Available tumor samples were identified and tested for HPV16 RNA to define HPV-driven OPC. Results: HPV16-E6 antibodies were present at baseline in 42.3% of 52 OPC patients and 0.5% of 924 control subjects. HPV16-E6 antibody levels were highly elevated and stable across serial blood samples for 21 OPC patients who were seropositive at baseline, as well as for one OPC patient who seroconverted closer to diagnosis. All five subjects with HPV16-driven OPC tumors were HPV16-E6-seropositive, and the four subjects with HPV16-negative OPC tumors were seronegative. The estimated 10-year cumulative risk of OPC was 6.2% (95% confidence interval [CI] = 1.8% to 21.5%) for HPV16-E6-seropositive men, 1.3% (95% CI = 0.1% to 15.3%) for HPV16-E6-seropositive women, and 0.04% (95% CI = 0.03% to 0.06%) among HPV16-E6-seronegative individuals. Conclusions: Forty-two percent of subjects diagnosed with OPC between 1994 and 2009 in a US cohort were HPV16-E6 seropositive, with stable antibody levels during annual follow-up for up to 13 years prior to diagnosis. Tumor analysis indicated that the sensitivity and specificity of HPV16-E6 antibodies were exceptionally high in predicting HPV-driven OPC.